2023
DOI: 10.1093/jaoacint/qsad002
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Investigation Between Raw and Stir-Frying Processed Cuscutae Semen Based on HPLC Fingerprints Coupled With Chemometric Methods

Abstract: Background The curative effect of Cuscutae Semen could be adjusted after stir-frying, and it’s difficult to distinguish between the raw Cuscutae Semen (CS) and stir-frying processed Cuscutae Semen (SFCS) in clinical practice. Objective The paper aims to establish the fingerprints of raw and fried Cuscutae Semen products by high performance liquid chromatography (HPLC) so that could analyze the compounds in raw and stir fried … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…23 In addition, Changli et al demonstrated that the processing temperature was a factor that led to changes in the content of six phytochemical compounds (neoclorogenic acid, cryptophyllogenic acid, caffeic acid, quercetin, isorhamnetin, and kaempferol) between raw and processed Semen Cuscutae. 24…”
Section: Changes In Chemical Constituentsmentioning
confidence: 99%
“…23 In addition, Changli et al demonstrated that the processing temperature was a factor that led to changes in the content of six phytochemical compounds (neoclorogenic acid, cryptophyllogenic acid, caffeic acid, quercetin, isorhamnetin, and kaempferol) between raw and processed Semen Cuscutae. 24…”
Section: Changes In Chemical Constituentsmentioning
confidence: 99%